Child Welfare Law, "Best Interests of the Child" Ideology, and First Nations - Kline, Marlee (Osgoode Hall Law Journal, 1992)
Liberalism has structured legal discourse such that racism is most often unintended and rarely explicit. To understand how and why law has an oppressive and discriminatory impact on First Nations and other racialized groups in Canadian society, one must look at some of its more subtle processes and, in particular, its ideological form. The goal of this article is to provide insight into the origins and operation of "best interests of the child" ideology and to illustrate how it structures and constrains judicial decision making in the context of First Nations child welfare. Best interests ideology serves to portray the apprehension and placement of First Nations children away from their families and communities as natural, necessary, and legitimate, rather than coercive and destructive. This is accomplished, in part, through legal processes that appear to be universal and neutral, and to protect children and serve their best interests. As well, the relevance and importance of a First Nations child maintaining her First Nations identity and culture is minimized. After illustrating the difficulty involved in transforming ideology through law reform, the article concludes by suggesting that First Nations must be empowered to develop their own child welfare services outside the framework of existing provincial legislative schemes and in line with more general goals of self-government.